Knowledge About Various Aspects of Diabetes Among Known Diabetic Patients Attending Diabetic Clinic at Pakistan Institute of Medical Sciences Hospital, Islamabad: Knowledge About Various Aspects of Diabetes Among Known Diabetic Patients - Qasim, Muhammad; Arshad Jamil, Muhammad; Hanif, Yasir; Maqsood Butt, Asif; Mahmood ul Hassan, Syed; Qasim, Sana (Pakistan Journal of Health Sciences, 2022)
Diabetes Mellitus (DM) knowledge of various aspects is critical for disease prevention, management, and control. Several studies, however, have consistently shown that the general population is unaware of diabetes. Objective: To assess Knowledge about various aspects of diabetes among known diabetic patients attending diabetic clinic at Pakistan Institute of Medical Sciences (PIMS) Hospital, Islamabad. Methods: During this descriptive cross-sectional study data were collected from 200 patients through a self-structured questionnaire. patient was questioned about their demographic information as well as their personal and diabetes-related history. Participants were asked to respond to each question in the questionnaire using their knowledge and understanding. Data were obtained in frequency and percentage to examine sociodemographic variables. Results: In the current study, more females, 108 (54 %) contributed in the study as opposed to males, 92 (46 %). Results showed that 170 (85%) of diabetic patients had type 2 diabetes, 24 (12.0 %) were suffering from type 1 diabetes, and 6 (3.0 %) had Gestational diabetes mellitus GDM. Conclusions: There was considerable knowledge about diabetes in known diabetic patients but still there is a dire need to increase knowledge and awareness regarding disease understandings, causes, complications, management, and its preventive measures.